Analytical study of the relationship between the biokenamatic variables of categorical scoring in basketball (Journal of the College of Basic Education, 2022)
Recognizing the values of some biokenamatic cvariables for cross-shooting in basketball and identifying the relationship between the values of some bio-kinematics variables for cutting-edge basketball. The researcher hypothesized that there is a significant relationship between the values of some biokinetic variables for the categorical scoring in basketball. The researcher used the descriptive method for its relevance to the nature of the research. The research sample was chosen by the intentional method, which consisted of (10) players out of (18) players who represented the youth of the Electricity Club Basketball for the year (2019-2020). Technical scientific and analysis as means of data collection. The researchers used video imaging to achieve technical scientific observation by using a Japanese-made yashica video camera with an internal memory (1 TB) placed at a distance of (8.90 meters) and to the right of the player and the height of the lens 1.35 meters from the surface The speed of the video camera was (160 images / second) and the following programs were used in the analysis, the maxtraq program - the kenova program. The researcher used the following statistical methods to process the data (arithmetic mean, standard deviation, simple correlation coefficient (Pearson), coefficient of variation) and the researchers concluded A set of conclusions The researcher recommended a set of recommendations.